Downhole seismic logging for detailed P-S waves velocity determination - KAMBOURIS, P. J.; ALEXOPOULOS, J. D.; PAPADOPOULOS, T. D. (Bulletin of the Geological Society of Greece, 2001)
Downhole seismic velocity logging has been used in detailed geotechnical surveys for engineering applications. Determination of dynamic elastic constants from acoustic velocity measurements is often a challenging procedure in case of highly variable unconsolidated overburden. Accuracy of Ρ - S cross-hole velocity measurements is greatly enhanced with the methodologies described. Severe ambiguities, primarily in direct shear wave arrivals picking are diminished, as a result of obtaining redundant data sets. Errors in the determination of zero time inherent to the electronic circuitry or following the use of drill bit or the SPT cone as seismic sources have been decreased by using the standard steel plate and the loaded shear wave plank as alternatives. Extensive AGC and frequency filtering is applied in order to increase the accuracy of the later arrivals. The picked times, corresponding to the overlapping data sets, are processed according to a method, which finally assigns a velocity value to each depth point.